Development of a Prototype Using the Internet of Things for Kinetic Gait Analysis - Caliskan, Muhammet; Tumer, Abdullah Erdal; Sengul, Sumeyra Busra (International Journal of Intelligent Systems and Applications in Engineering, 2018)
The proliferation of mobile devices and the gradual development of technology have led to the emergence of the concept of Internet of Things. The Internet of Things has led to an increase in the work done especially on the medical field. At the beginning of the reasons for using the Internet of Things in medical studies is to be able to detect and display instantaneous changes that physicians can not even observe. Another important cause is that it allows the patient to be observed in the natural world. This is especially true in gait analysis, where a natural gait must be measured for accurate diagnosis. This study is concerned with the use of Internet of Things technology in gait analysis. To follow the foot pressure distribution in the study, a prototype was installed in shoes using the Internet of Things. The prototype consists of a thin, flexible base that collects analog data from the 32 sensors and transmits it wirelessly to mobile or PC computers via Bluetooth technology. The software developed by the prototype shows the pressure on every small sensor in the room and draws a walking graph. The accuracy and reliability of the prototype were evaluated by preliminary experimental measures. The results show that the system has the capacity to reliably measure pressure distributions of the sole of the foot.